Expanding Perspectives on Alternative Children’s Literature / Alt Kid Lit: What Kids’ Literature Might Be - Stolz, Devon (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2024)
This review of Alt Kid Lit: What Kids’ Literature Might Be, edited by Kenneth B. Kidd and Derritt Mason, explores the anthology’s analysis and reframing of children’s and young adult (CYA) literature that exists outside of normative print culture. The review focuses on the text’s emphasis on diversity and interdisciplinary approaches to critiquing mainstream print culture and the exclusionary world of CYA studies and publishing. Exploration of the book’s 13 essays, 2 interviews, and a panel discussion and the themes contained within reflects the pedagogical value inherent when marginalized perspectives and texts are given the attention they deserve. Overall, Alt Kid Lit is praised for its significant contributions to CYA scholarship and its potential to make lasting contributions in the work of scholars, educators, and librarians working with CYA literature and readers.